2013
DOI: 10.1037/a0033538
|View full text |Cite
|
Sign up to set email alerts
|

Work–family enrichment among dual-earner couples: Can work improve our family life?

Abstract: The extent to which resources generated at work and positive affect were associated with enrichment in the family domain among 107 dual-earner couples was investigated. Grounded in work-family enrichment theory (Greenhaus & Powell, 2006), this study examined the indirect effect of workplace organizational support on family satisfaction through positive affect at work. Organizational support for work-family management was associated with positive affect at work for both women and men, and positive affect at wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 41 publications
1
17
0
Order By: Relevance
“…Another explanation may be that because women are more satisfied with their parental role (due to perceptions of higher workplace family support, among other aspects), they may reduce demands on their partners for higher family involvement, therefore reducing their partners' perceptions of role conflict. In fact, Dunn and O'Brien () reinforced this explanation. The authors found that if mothers are happy (positive affect) with their work due to workplace family support, the time spent with the family reflects this satisfaction.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…Another explanation may be that because women are more satisfied with their parental role (due to perceptions of higher workplace family support, among other aspects), they may reduce demands on their partners for higher family involvement, therefore reducing their partners' perceptions of role conflict. In fact, Dunn and O'Brien () reinforced this explanation. The authors found that if mothers are happy (positive affect) with their work due to workplace family support, the time spent with the family reflects this satisfaction.…”
Section: Discussionmentioning
confidence: 94%
“…In this line of reasoning, Demerouti () showed that resourceful work environments augment levels of employee energy, which is transmitted to the partner by increasing the partner's home resources. Similarly, Dunn and O'Brien () found family satisfaction of fathers to be predicted by the positive affect of mothers at work, caused by mothers' workplace family support.…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…Where non-equivalent groups are concerned, researchers must take appropriate action to eliminate the possibility of a Type I error. A recent study by Dunn and O’Brien (2013) found that dual-earner couples with children enjoyed positive affect from work–life programs. The authors however, intimated that demographic homogeneity among study participants limited generalizability of results.…”
Section: Discussionmentioning
confidence: 99%